Advocacy Research on Homophobia in Education: Claims-Making, Trauma Construction and the Politics of Evidence. (February 2020) - McCormack, Mark
Sociology has an ambivalent relationship with advocacy research because the benefits of participation and engagement must be balanced with concerns about bias. The current study uses 10 recent research reports on homophobia in British educational settings, written and funded by campaigning charities, as a case study of contemporary advocacy research. Presenting a sociological analysis of these documents and adopting a social problems approach, claims-making processes in the reports are documented and significant methodological and analytical flaws are identified. Instead of objective research, these reports are campaigning documents that seek to gain media coverage and influence policy. Implications for how the reports should be used as resources for research and social policy are examined, and a more nuanced and sophisticated approach to engaging with advocacy research is called for.